Genome-Wide Analysis of the HSP20 Gene Family and Expression Patterns of HSP20 Genes in Response to Abiotic Stresses in Cynodon transvaalensis - Cui, Fengchao; Taier, Geli; Wang, Xiangfeng; Wang, Kehua (Frontiers in Genetics, 2021)
African bermudagrass (Cynodon transvaalensis Burtt-Davy) is an important warm-season turfgrass and forage species. Heat shock protein 20 (HSP20) is a diverse, ancient, and important protein family. To date, HSP20 genes have not been characterized genome-widely in C. transvaalensis. Here, we confirmed 41 HSP20 genes in C. transvaalensis genome. On the basis of the phylogenetic tree and cellular locations, the HSP20 proteins were classified into 12 subfamilies. Motif composition was consistent with the phylogeny. Moreover, we identified 15 pairs of paralogs containing nine pairs of tandem duplicates and six pairs of WGD/segmental duplicates of HSP20 genes. As expected, the orthologous genes revealed that C. transvaalensis had a closer evolutionary relationship with monocots (maize and rice) than dicots (Arabidopsis and soybean). The expression patterns of HSP20 genes were identified with the transcriptome data under abiotic stresses. According to the expression profiles, HSP20 genes could be clustered into three groups (Group I, II and III). Group I was the largest and these genes were upregulated in response to heat stress. A total of 938 cis-elements were captured in the putative promoters of HSP20 genes. Almost half of the cis-elements were stress-responsive, indicating the expression pattern of HSP20 genes under abiotic stresses might be largely regulated by the cis-elements. Additionally, three-dimensional structure simulations and protein-protein interaction networks were incorporated to resolve the function mechanism of HSP20 proteins. In summary, the findings fulfilled the HSP20 family analysis and could provide useful information for further functional investigations of the HSP20 family in C. transvaalensis.